International Wildlife Trafficking: A perspective on the challenges and potential forensic genetics solutions. (September 2021) - Smart, Utpal; Cihlar, Jennifer Churchill; Budowle, Bruce
Abstract: International wildlife trafficking (IWT) is a thriving and pervasive illegal enterprise that adversely affects modern societies. Yet, despite being globally recognized as a threat to biodiversity, national security, economy, and biosecurity, IWT remains largely unabated and is proliferating at an alarming rate. The increase in IWT is generally attributed to a lack of prioritization to curb wildlife crime through legal and scientific infrastructure. This review: (1) lays out the damaging scope and influence of IWT; (2) discusses the potential of DNA marker systems, barcodes, and emerging molecular technologies, such as long-read portable sequencing, to facilitate rapid, in situ identification of species and individuals; and (3) encourages initiatives that promote quality and innovation. Interdisciplinary collaboration promises to be one of the most effective ways forward to surmounting the complex scientific and legal challenges posed by IWT. Highlights: International Wildlife Trafficking (IWT) is a pervasive yet largely unabated illegal enterprise. IWT's impacts on biodiversity, national security, economy and biosecurity are well documented. The U.S. is one of the largest importers of illegal wildlife, and needs to do more to counter IWT. Genetic identification approaches used in human forensics, need to be more widely used in wildlife forensic genetics. Wildlife forensic genetics needs more education, training and funding, than currently available for research and development.